Modeling the effect of cochlear windows activity on reverse stimulation under the role of physiological third windows. (1st December 2020) - Liu, Houguang; Xue, Lin; Yang, Jianhua; Liu, Wen; Yang, Shanguo; Wang, Wenbo
Highlights: Hybrid circuit model of human ear considers the cochlear and vestibular aqueducts. Round window stiffness is predicted to increase 10-fold caused by otitis media. Third windows complicate the resonant response of the auditory system. Third windows mitigate the deterioration of the reduced cochlear windows activity. Abstract: The cochlear windows consist of the round window (RW) and the oval window (OW). These two openings connect the cochlea and the middle ear; its activity plays a vital role in sound transmission into the cochlea. However, it is difficult to capture a brief description of how cochlear windows activity affects reverse stimulation with physiological third windows. In the present study, a hybrid circuit model considering the vestibular and cochlear aqueducts was used to investigate the relationship between cochlear windows activity and reverse stimulation. Meanwhile, a finite element (FE) model of the RW was established to perform stiffness calibration on the RW thickening. Then, middle ear disorders involving the activity of the RW and the OW were simulated: otosclerosis and otitis media. Finally, the intracochlear differential pressure transfer function were calculated to predict the influence of cochlear windows activity on sound perception under reverse stimulation. The results show that the resonant response of the auditory system complicates the effects of cochlear windows activity on reverse sound transmission. Moreover, the physiological third windows produce volume velocity shunt flow, which mitigates the deterioration caused by the reduced cochlear windows activity during reverse stimulation.